PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WORDWALL PADA MATERI DAUR ULANG LIMBAH DALAM PEMBELAJARAN SENI BUDAYA KELAS V SEKOLAH DASAR - Cindi Sandra; Destrinelli; Indra Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arts and Culture Education plays an important role in developing creativity, art appreciation, and environmental awareness of elementary school students. However, Arts and Culture learning on waste recycling material in grade V of SD Negeri 182/I Hutan Lindung is still dominated by conventional methods without the support of technology-based interactive learning media, so that students tend to be passive, less enthusiastic, and have difficulty in understanding the material and developing creativity. This study aims to develop a Wordwall-based educational game media on waste recycling material and to determine its level of validity and practicality in learning. This study uses the Research and Development (R&D) method with a 4D model that includes the Define, Design, Develop, and Disseminate stages. The research subjects were grade V students of SD Negeri 182/I Hutan Lindung. Data were collected through interviews, observations, and validation and practicality questionnaires given to material experts, media experts, linguists, teachers, and students. The results of the study showed that the developed media had a very good level of validity, namely 90% for material experts, 80% for media experts (valid), and 100% for linguists. The practicality test results were categorized as very practical, with an average score of 3.72 in the small group test and 3.76 in the large group test, and a teacher assessment of 5.0. Furthermore, the developed media was also proven to increase student engagement, activeness, and interest in learning Arts and Culture. Therefore, the Wordwall-based educational game media was declared valid, practical, and suitable for use in Arts and Culture learning using waste recycling materials.